A influência das técnicas de haute couture na produção criativa de moda e na agregação de valor ao vestuário - Carmo, Tanlin Nishimura (2015)
The luxury market, share the main French maisons because of the orbtained results and since the last decades is in high grow. This fact to beyond of presenting positive in the finance aspect also is to the constant development and upgrading, for example, the various luxury articles, that includes the ready to wear dressing room, in special the haute couture, an exclusive product of high cost which presents as source of consumes, by one side, and, by other of investment, how business, jobs generating, income, taxes, whatever, crucial product for this specific market. In this context and over this positive perspective is that job rises up to concept this market even on international ambit as national ambit, with looks to the historic registry of luxury articles, beyond of explain it over social, physcologic and politic perspectives how a concept applied in the development of trademarks and products. One of the segments which get more money with this market is fashion. In this way, in a short form, this work pretends show the universe of the French high couture through of historic study about the born, evolution, importance, and maintance through the ages until nowadays. Among the utilized techniques which aggregate emotional value to the production of the high couture opted by embroidery, what shows itself in many different options, however, the choosen one, not just because of beauty, but, above all because of complexity and fine finish, the Lunéville Crochet. The emotional design is detached, has been seen used on experimental way in development of trademark and collection to detach the concept of luxury, outstanding characteristic of high couture production.